Adjuvant-driven antibody response to use cows as biofactories of anti-SARS-CoV-2 neutralizing antibodies in colostrum - E.B. Gaspar; D.J.B. Orts; H.H.M. Costa; P.E.A. Souza; N.T.B.S. Honório; C.R. Prudêncio; L.P. Silva; C.C. Bonatto; A.P.A. Bastos; P.P. Adriani; G.S. de Oliveira; R. Domingues; et al. (Journal of Dairy Science)
ABSTRACT: Cows produce a substantial amount of immunoglobulin in the colostrum, and nutraceutical products derived from these antibodies are gaining attention for their potential role in human viral disease prevention. The objective of our study was to develop an immunization schedule for pregnant cows to produce hyperimmune colostrum with antibodies presenting high avidity and neutralizing activity against SARS-CoV-2. The recombinant spike receptor-binding domain (RBD) from SARS-CoV-2, expressed using the Expi293F system and purified via Ni-affinity chromatography, was solubilized in (1) saponin (QuilA) or (2) a suspension of potassium and aluminum hydroxide (Alum). Vaccination of pregnant cows and serum sample collection were performed 45, 30, and 15 d before the expected calving date. Serum and colostrum were also collected on the day of parturition. Anti-RBD IgG, IgG1, and IgG2 production, viral neutralization, and antibody avidity were evaluated by ELISA. Cows immunized with recombinant RBD with the QuilA adjuvant produced higher amounts of all antibody subclasses than cows in the Alum group. The viral neutralization index from serum samples was also higher in the QuilA group. Significant differences were not observed in the avidity of antibodies, except for that of IgG2, which was higher in the serum of cows receiving the Alum formulation. As the IgG1 antibody subclass and its avidity are crucial for SARS-CoV-2 neutralization, QuilA might be the optimal adjuvant for producing hyperimmune colostrum in cows. These findings support the use of cows as biofactories of neutralizing antibodies against SARS-CoV-2 or any future emerging and re-emerging viral diseases, with the possibility of simply substituting the subunit antigen in the vaccine formulation. Further tests must be done to evaluate the efficacy of using hyperimmune colostrum as a nutraceutical or purified bovine antibodies as a pharmacological approach for COVID-19 prevention.